2017
DOI: 10.3747/co.24.3561
|View full text |Cite
|
Sign up to set email alerts
|

Oral Chinese Herbal Medicine as Maintenance Treatment after Chemotherapy for Advanced Non-Small-Cell Lung Cancer: A Systematic Review and Meta-Analysis

Abstract: BackgroundThe concept of maintenance therapy in cancer treatment is currently under debate because of modest

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…Today, TCM is an accepted and important part of cancer treatment alongside Western medicine in China and is gaining acceptance in the United States. (Liu et al, 2015;Ling et al, 2018;Wang Q. et al, 2017;Xiang et al, 2019). Complementary medicine has increased 30% in National Cancer Institute (NCI) designated cancer centers, and acupuncture is represented in 73% of those centers, herbal medicine in 66.7% (Yun et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Today, TCM is an accepted and important part of cancer treatment alongside Western medicine in China and is gaining acceptance in the United States. (Liu et al, 2015;Ling et al, 2018;Wang Q. et al, 2017;Xiang et al, 2019). Complementary medicine has increased 30% in National Cancer Institute (NCI) designated cancer centers, and acupuncture is represented in 73% of those centers, herbal medicine in 66.7% (Yun et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…With the development in pharmacology, the constituents of many Chinese herbal medicines have been separated. Therefore, the mechanisms of Chinese herbal medicines for disease treatment have gradually become clear, and in recent years an increasing number of studies have applied Chinese herbal medicine in the treatment of cancer . Therefore, this study explored the effects of the herbal medicine E. prostrata extract (EPE) on oral cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reviews have suggested that adjunct CAM therapies, including acupuncture, pharmacopuncture, and herbs, have benificial effects on cancer-related symptoms, conventional treatment-associated side effects, and the response rate of the tumor. [ 27 – 34 ] However, limited cohort evidence has been published on its effects on survival and quality of life for patients being treated with TKM. The objective of this prospective cohort study is to evaluate both the effect of ACTKMT on EFS, DFS/PFS, OS, quality of life, blood test results, and telomere length and the adverse events associated with ACTKMT.…”
Section: Discussionmentioning
confidence: 99%